Neonatal outcomes of singleton live births with vanishing twin syndrome following double embryos transfer in assisted reproductive technology: a retrospective cohort study - Yan, Junfang (J Ovarian Res, 2019)
BACKGROUND: Women with vanishing twin syndrome are associated with increased risks of adverse neonatal outcomes, such as preterm birth (PTB) and low birthweight (LBW), compared with those in singleton live births following single embryo transfer (SET) in assisted reproductive technology (ART). METHODS: Anonymized data on all cycles performed in China were obtained from the Reproductive Medicine Department at the Third Affiliated Hospital of Zhengzhou University, which had involved 127597 cycles following double embryos transfer (DET), including 54585 fresh embryos transfer (ET) cycles and 73012 frozen embryos transfer (FET) cycles. In addition, the obstetric outcomes, such as gestation age, PTB, small for gestation age (SGA), birthweight (BW), LBW, congenital malformation, pediatric admission and Neonatal Intensive Care Unit (NICU) admission in the fresh ET and FET cycles, were analyzed. Moreover, logistic regression analysis was performed to adjust the confounders, including age of women, body weight index (BMI), value of AMH, infertile years, current cycle, antral follicles, cause of infertility, number of oocytes retrieved, endometrial thickness at the date of transplantation, number of high-quality embryos, and embryo stage. RESULTS: In the fresh ET cycles, the BW and gestational age in study group were lower than those in control group, which were (2962.4 ± 563.1vs. 3104.9 ± 498. 5, p = 0.000) and (262.8 ± 8.4 vs. 268.9 ± 13.9, p = 0.000), respectively. Relative to control group, the study group was linked with increased risks of PTB (adjusted odds ratio (aOR) 2.45, 95% CI:1.98–3.03, adjusted p = 0.000), LBW (aOR2.11, 95% CI:1.67–2.65, adjusted p = 0.000), pediatric admission (aOR 2.55, 95% CI2.07–3.13, adjusted p = 0.000), and NICU admission (aOR 1.98, 95% CI1.32–2.96, adjusted p = 0.001), but there were no statistically significant differences in the risks of SGA (aOR 1.09, 95% CI0.82–1.45, adjusted p = 0.960) and congenital malformation (aOR 0.94, 95% CI0.53–1.68, adjusted p = 0.640) between the two groups. In the FET cycles, the gestational age and BW in study group were lower than those in control group, which were (263.0 ± 15.7vs. 273.0 ± 10.5, p = 0.000) and (3099 ± 662.1vs. 3352 ± 671.5), respectively. The study group was associated with increased risks of PTB (aOR2. 45, 95% CI: 2.23–3.43, adjusted p = 0.000), LBW (aOR 2.67, 95% CI: 2.13–3.34, adjusted p = 0.000), pediatric admission (aOR2.62, 95% CI2.14–3.21, adjusted p = 0.000), and NICU admission (aOR 2.22, 95% CI1.43, 3.46, adjusted p = 0.001) compared with those in control group, but differences in the risks of SGA (aOR 0.98, 95% CI0.71–1.36, adjusted p = 0.730) and congenital malformation (aOR 0.99, 95% CI 0.60,1.63, adjusted p = 0.940) between the two groups were not statistically significant. CONCLUSIONS: Our study finds that singleton live births with VTS have higher risks of LBW, PTB, pediatric admission and NICU admission than those without VTS in both the fresh and frozen cycles, even after adjusting for confounders. However, no increased risks of SGA or congenital malformation are observed in singleton live births in both the fresh and frozen ART cycles following DET.